Optimum Design and Performance of Porous Concrete for Heavy-Load Traffic Pavement in Cold and Heavy Rainfall Region of NE China - Ailing Yao; Hao Ding; Xiaochen Zhang; Zhao Hu; Runshu Hao; Tao Yang (Advances in Materials Science and Engineering)
The aim of the study was to solve the problem of drainage stability of pavement base in cold and Cloudburst area. With porous concrete as the research object, an optimum design of porous concrete was determined using a step filling and orthogonal test method, and the relationship between the porosity and the connected porosity of the porous concrete was analyzed. Furthermore, drainage performance and frost resistance of the pavement, compressive strength of the porous concrete, bending strength, and compressive elastic modulus were studied. The results show that the effects of water-cement ratio on the strength of porous concrete based on the step filling method are the most significant. In addition, the connected porosity and goal porosity have a good linear relationship; that is, the drainage performance increases with the increase in connected porosity, whereas the frost resistance, compressive strength, flexural tensile strength, and compressive elastic modulus decrease with the increase in connected porosity. Based on an engineering project in Inner Mongolia (in China), it was shown that porous concrete with a goal porosity of 15% used as a pavement base could meet the requirements of cold weather, showers, and heavy traffic.